2021
DOI: 10.1177/11206721211064469
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors in central retinal vein occlusion: A multi-center case-control study conducted on the Italian population

Abstract: Purpose To explore the risk factors for central retinal vein occlusion (CRVO) by comparing a large sample of patients with healthy controls. Materials and Methods Multi-center case-control study. The study group includes patients affected by central retinal vein occlusion, confirmed angiographically, aged 50 years old or above (Group A). The control group includes healthy subjects without an history of retinal vein occlusion (Group B). Outcome measures: age, gender, active smoking, presence of uncontrolled art… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 27 publications
0
12
0
1
Order By: Relevance
“…However, further research also highlights the need for a comprehensive assessment of cardiovascular risk factors. In an Italian analysis, in addition to nicotine abuse, poorly controlled arterial hypertension, diabetes mellitus type 2, dyslipidemia, carotid artery stenosis, and sleep apnea syndrome were found dispropor- tionately often in patients with RVO [40]. These findings are also consistent with the database analysis of over 23 million insured persons from Korea, who were monitored over a period of 4 years and for whom an increased risk of RVO in the presence of a metabolic syndrome was described (hazard ratio 1.46) [36].…”
Section: Retinal Vein Occlusions (Rvo)mentioning
confidence: 99%
See 1 more Smart Citation
“…However, further research also highlights the need for a comprehensive assessment of cardiovascular risk factors. In an Italian analysis, in addition to nicotine abuse, poorly controlled arterial hypertension, diabetes mellitus type 2, dyslipidemia, carotid artery stenosis, and sleep apnea syndrome were found dispropor- tionately often in patients with RVO [40]. These findings are also consistent with the database analysis of over 23 million insured persons from Korea, who were monitored over a period of 4 years and for whom an increased risk of RVO in the presence of a metabolic syndrome was described (hazard ratio 1.46) [36].…”
Section: Retinal Vein Occlusions (Rvo)mentioning
confidence: 99%
“…Eine ältere Analyse hat ein erhöhtes Vorkommen noch verneint[34].Die Notwendigkeit einer umfassenden Beurteilung der kardiovaskulären Risikofaktoren ergibt sich aber auch aus weiteren Untersuchungen. In einer italienischen Analyse wurde neben dem Nikotinabusus auch ein nicht optimal eingestellter arterieller Hypertonus, ein Diabetes mellitus Typ 2, eine Dyslipidämie, eine Karotisstenose und ein Schlafapnoe-Syndrom überdurchschnittlich häufig bei Patienten mit RVV gefunden[40]. Diese Befunde passen auch zur Datenbankanalyse von über 23 Mio.…”
unclassified
“…Retinal vein occlusion (RVO) is one of most common retinal vascular disease, second only to diabetic retinopathy, and more common in older patients ( Ren et al, 2022 ). The pathogenesis of RVO is related to many factors such as vascular endothelial damage, hemodynamic changes, intraocular pressure, and ocular local compression ( Terao et al, 2022 ; Trovato Battagliola et al, 2022 ). In addition, the disease is closely related to arteriosclerosis, cardiovascular and cerebrovascular diseases, hypertension, diabetes, and other risk factors ( Orskov et al, 2022 ; Tang et al, 2022 ).…”
Section: Application Of Artificial Intelligence In Retinal Vascular D...mentioning
confidence: 99%
“…[25] However, most of the previous studies that aimed to explore the relationship between SDB and RVO in adults were of limited scale and have rarely been comprehensively evaluated in a meta-analysis. [26][27][28][29][30][31][32] Therefore, we performed a meta-analysis to systematically observe the relationship between RVO and SDB and to explore whether the association is consistent for different types of RVO (CRVO and BRVO) and in patients with SDB of differing severity.…”
Section: The Authors Have No Funding and Conflicts Of Interest To Dis...mentioning
confidence: 99%
“…Subsequently, 25 additional studies were excluded for the reasons shown in Figure 1, which led to 7 studies being finally selected for inclusion in the meta-analysis. [26][27][28][29][30][31][32]…”
Section: Study Identificationmentioning
confidence: 99%